Parallel corpus of Spanish, English and Chinese and corpus-based contrastive analysis of the past tense in Spanish (Linguamática, 2021)
This study constructed a trilingual parallel corpus, the Parallel Corpus of Spanish, English and Chinese (CPEIC in Spanish), and used it to benefit research in translation, contrastive analysis, language learning, and teaching. The CPEIC contains the world’s 3 most-spoken languages and comprises approximately 4 million data. Based on the construction result, a parallel corpus-based contrastive analysis was dedicated to the study of the past tense, which functions differently in the 3 languages. The results (1) support previous studies in associating the Spanish preterit and the Chinese aspectual marker "le", and in relating the Spanish imperfect with the English "would" and "was/were+Ving", (2) contradict assumptions for connecting the Spanish imperfect with the Chinese aspectual marker "zhe", and (3) offer new insights in uniting the Spanish preterit with the passive voice in all 3 languages.
Keywords: parallel corpus; translation; contrastive analysis; past tense; aspect; corpus-based